Experimental studies on the performance of dehumidifier using calcium chloride as a liquid desiccant. (2018) - Seenivasan, D.; Selladurai, V.; Arjunan, T.V.
The performance of liquid desiccant air conditioning system (LDAS) mainly depends on dehumidifier of the system. In this study, the effects of inlet parameters on the performance of liquid desiccant dehumidifiers were studied with and without indirect evaporative cooler or intercooler (IDEC) between the dehumidifier for single stage and double stage. The results show that: i) the dehumidification effectiveness decreases by 8.6% for the all types considered here, with increase in air flow rate from 0.05 kg/s to 0.11 kg/s; ii) the dehumidifier effectiveness decreases due to decrease of moisture removal rate with increasing desiccant temperature in all stages; iii) the moisture condensation rate and dehumidifier effectiveness increases by 30% and 22.67% respectively with increase in desiccant flow rate; iv) the moisture condensation rate is increased by 13% in increasing desiccant concentration. It is concluded that double stage desiccant dehumidifier with indirect evaporative cooler performs better.